2008
DOI: 10.1373/clinchem.2008.112243
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Recurrent Venous Thromboembolism by Endogenous Thrombin Potential and D-Dimer

Abstract: BACKGROUND:Increased thrombin generation is associated with an increased risk of recurrent venous thromboembolism. We investigated the relation between endogenous thrombin potential (ETP) and risk of recurrent venous thromboembolism and evaluated whether prediction of recurrence can be improved by a combined analysis of ETP and D-dimer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
105
2
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(123 citation statements)
references
References 20 publications
7
105
2
5
Order By: Relevance
“…Besser et al [92] reported that high ETP measured in the absence of thrombomodulin could indicate the patients at risk of a recurrence especially following an unprovoked episode. Those results were confirmed by Eichinger et al [80].…”
Section: Thrombin Generation As Marker For Recurrence Risksupporting
confidence: 72%
See 1 more Smart Citation
“…Besser et al [92] reported that high ETP measured in the absence of thrombomodulin could indicate the patients at risk of a recurrence especially following an unprovoked episode. Those results were confirmed by Eichinger et al [80].…”
Section: Thrombin Generation As Marker For Recurrence Risksupporting
confidence: 72%
“…As in other studies [92,80] on cohorts with high prevalence of the FV Leiden mutation, no thrombomodulin was added to the thrombin generation assay. This was decided so as not to decrease the sensitivity of the CAT ® assay for recurrent venous thrombosis due to the effect of the common FV Leiden mutation on the assay result (18), as the presence of FV Leiden in its heterozygous variant has not been associated with significant increase in the recurrence risk by most studies in the field [95,96].…”
Section: Discussionmentioning
confidence: 99%
“…A thrombin generation curve is produced from which parameters such as peak thrombin generation and the area under the thrombin generation curve (the ETP) are derived. Such measures have been used to predict, for example, risk of venous thromboembolism (10). The aim of this investigation was therefore to determine the impact that microparticles have on thrombin generation as measured by the Calibrated Automated Thrombogram V R (CAT) thrombin generation assay.…”
mentioning
confidence: 99%
“…First is the Calibrated Automated Thrombogram (CAT), a plate-based assay that measures the rate of thrombin generation and inhibition in citrated plasma, and has been used to quantify procoagulant activity in several diseases including VTE and coronary artery disease. [8][9][10] The clinical utility of in vitro thrombin generation however, remains to be determined in trauma patients. The objective of this study was to characterize and quantify procoagulant activity and MP in plasma obtained from individuals after traumatic injury.…”
Section: Discussionmentioning
confidence: 99%